Combined effects of dry-wet cycles and sustained loads on the seismic behavior of TRC-strengthened RC columns. (October 2021) - Li, Yao; Yin, Shiping; Lv, Henglin
Abstract: To study the seismic behavior of reinforced concrete (RC) columns serviced in coastal areas and strengthened with textile-reinforced concrete (TRC) after a dry-wet cycle coupled with a sustained load, low cycle loading testing was performed with six RC columns strengthened with TRC and one control column without TRC. The sustained stress ratio of the control column during the dry-wet cycle was 0.4 while those of the others strengthened with TRC were 0, 0.2, 0.4 and 0.6. The results show that although chloride dry-wet cycles decrease the ductility and energy dissipation capacity of strengthened columns, compared with the control column, TRC could still delay stiffness degradation and increase the ductility of strengthened columns to a certain extent. Additionally, with an increase in the sustained stress ratio, the energy dissipation capacity of the specimens decreases. The peak loads of the specimens gradually decrease with increasing sustained stress ratio during loading in the forward direction, and the variation in the peak load is irregular during loading in the negative direction. Besides, a reasonable proportion of the vertical load could improve the seismic capacity of unstrengthened specimens under chloride corrosion.